PENGARUH PEMBERIAN MINUMAN FUNGSIONAL PISANG-ROSELLA TERHADAP PENURUNAN TEKANAN DARAH DI POSBINDU PRIMA NUGRAHA - Vera Asti Rahmawati; Setyo Prihatin; Arinthina Rahayuni; Yuniarti Yuniarti (JURNAL RISET GIZI, 2018)
Background :Highblood pressure or hypertension is a progressive health disorder when the systolic and diastolic blood pressure stage on 140 mmHG / 100 mmHg or more. Non pharmacological such as diet can use to prevent hypertension, there was in DASH diet decrease sodium intake, increase potassium and antioxidant anthocyanin intake. Potassium and anthocyanins as diuretic and vasodilator that can lower blood pressure. Objective : To know the influence of functional banana-rosella’s drinking on decrease blood pressure in Posbindu Prima Nugraha. Methods :The type of research is True-Experimental with the design of pre and post test control group design. Sampling using random sampling technique to get 12 treatment samples and 12 control samples. Data collected were anthropometric data, potassium sodium intake and diastolic systolic blood pressure data and consumption compliance rate. The statistical test used is independent t-test and ANOVA Repeated Measure test. Results: Nutritional status of the sample included good nutritional status category. Sodium intake of the sample included high category and potassium was low category for each group. Levels of compliance consumption of functional banana-rosella’s drinking ≥ 80%, despite a decrease in consumption on day-5. There is effect of functional banana-rosella’s drinking on decreasing systolic blood pressure at 4.92 mmHg in the 4th day intervention (p value = 0.047), but it does not affect the decrease of diastolic blood pressure (p value = 0.650). Conclusions: Functional banana-rosella’s drinking can significantly lower systolic blood pressure, but do not indicate for diastolic blood pressure.